Information and Communication Technology as a Mediator of Infrastructure, Labor Quality, and Investment Effects on Regional Economic Growth in Indonesia - Wiyan Mailindra; Syamsurijal Tan; Heri Berta; Syaparuddin (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose – Modern economic growth relies not only on physical accumulation but also on digital integration. This paper examines how Information and Communication Technology (ICT) acts as a mediator in the relationship between conventional macroeconomic variables infrastructure, labor quality, domestic investment (PMDN), and foreign investment (PMA) and economic growth in Indonesia. Design/methodology/approach – This quantitative study uses panel data from 34 provinces in Indonesia during the period 2018–2024 (238 observations). The study applies panel data econometric methods to analyze the mediating role of ICT in the relationship between infrastructure, labor quality, investment, and regional economic growth in Indonesia. Finding/Results – The results show that infrastructure, labor quality, PMDN, PMA, and ICT significantly contribute to economic growth in Indonesia. ICT significantly mediates the effects of infrastructure, PMDN, and PMA on economic growth, but does not significantly mediate the relationship between labor quality and economic growth. Originality/Value – This study introduces IP-TIK as the "missing link" explaining why traditional macro variables often fail to yield optimal growth in developing regions. The main take-home message is that physical infrastructure and investments must be integrated with digital ecosystem development to achieve inclusive economic growth.